2013
DOI: 10.1016/j.ygyno.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Multiple large bowel resections: Potential risk factor for anastomotic leak

Abstract: Objectives Identify risk factors of anastomotic leak (AL) after large bowel resection (LBR) for ovarian cancer (OC) and compare outcomes between AL and no AL. Methods All cases of AL after LBR for OC between 01/01/1994-05/20/2011 were identified and matched 1:2 with controls for age (+/−5years), sub-stage (IIIA/IIIB;IIIC;IV), and date of surgery (+/−4years). Patient-specific and intraoperative risk factors, use of protective stomas, and outcomes were abstracted. A stratified conditional logistic regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 62 publications
5
55
0
1
Order By: Relevance
“…This is in line with previous studies. 11,14 With respect to the prognostic implication of AL, it has to be kept in mind that the number of events, that is, patients with AL (n = 9), was limited in the present study. Anastomotic leakage was associated with shortened PFS and OS in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies. 11,14 With respect to the prognostic implication of AL, it has to be kept in mind that the number of events, that is, patients with AL (n = 9), was limited in the present study. Anastomotic leakage was associated with shortened PFS and OS in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The author demonstrated that the addition of another large bowel resection to rectosigmoidian resection associated with a significantly higher risk of anastomotic leak (p=0.025) while the decision of performing a protective ileostomy significantly decreased the risk of anastomotic leak (p=0.024). In the same study, other factors such as BMI value, ASA score, diabetes mellitus or smoking did not significantly influence the apparition of anastomotic leaks (23).…”
Section: Discussionmentioning
confidence: 67%
“…5,7 Additional risk factors such prior pelvic radiation, anastomosis of less than 6 cm from the anal verge, failed leak test, or contamination of the pelvis with stool have been also reported. 13 In an effort to identify the indications for DI in the context of primary debulking surgery for ovarian cancer, only 2 factors were found to be associated with the decision of performing a DI: extended operating time and increased length of rectosigmoid resection.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,12,14 Nonetheless, because of the lack of prognostic scores of AL, there is no clear indication regarding which cases would and would not benefit from DI. Ultimately, the surgeon has the choice to selectively perform a DI in case of colorectal anastomosis.…”
mentioning
confidence: 99%